Biocharcoal dari Kulit Rambutan (Nephelium lappaceum L.) sebagai Adsorben Zink dan Tembaga - Setiawan, I Ketut Ardi; Napitupulu, Mery; Walanda, Daud K. (Universitas Tadulako, 2018)
Rambutan peel is one source of biocharcoal production to adsorb metal ions because of the potential of cellulose content. This study aimed to describe the characteristics of biocharcoal from rambutan peel as well as to determine biocharcoal adsorption to zinc and copper based on the variation of biocharcoal weight and metal ions concentrations. The method used in this study was a laboratory experiment, and metals were analyzed using spectrophotometer spectroDirect. The results showed the moisture and ash levels of the biocharcoal were 0.4% and 5.4%, respectively. The optimum weight of biocharcoal to adsorb Zn and Cu ions was 40 mg with their percentage adsorption of 98.81% and 98.94%, respectively. The optimum concentration adsorption of biocharcoal to Zn ions was 40 ppm with the percentage adsorption of 98.32%, while for the Cu ions was 60 ppm with the percentage adsorption of 98.25%.